Investigating Students’ Engagement in ESP Online Course during Covid-19 Pandemic - Risa Arroyyani (Journal of English Language and Education, 2021)
This research aims to determine students’ engagement levels and factors in attending ESP online courses during the Covid-19 pandemic. In performing data and data analysis, a qualitative research design was employed with the interpretation of descriptive statistics. This research distributed a questionnaire to 59 students in the nursing department. The research findings showed that four dimensions of students’ engagements got a means score in the level of "Agree"; skills engagement with 4.18, participation/interaction engagement with 3.99, emotional engagement with 3.88, and performance engagement with 3.86. For factors influencing students' engagement, all factors consisting of direct and indirect factors got a means score of "Strongly Agree" as 4.38. The findings showed that the students were engaged in an ESP online course. Both direct and indirect factors influence students’ engagement including learning resources, teaching competency, knowledge base, learning style, teaching context, social network, and technology.